Historical and Cultural Description of Zhyrau and Skills of Talkers and Translators (Journal of history, 2019)
Historical and cultural description of Zhyrau and mastery of storytellers and translators. The article is devoted to the precious legacy of poetry zhyrau. The article reveals the rich poetry of Zhyrau, their content and properties, as well as the poetics of Kazakhs, as the Kazakh people attached special importance to the art of eloquence and the language of feelings – poetry. The problem of translating zhyrau into Russian is considered.